Survey of the Water Resources Collection at the James H. Albertson Center for Learning Resources - Van Horn, Carole J (University of Wisconsin-Stevens Point, College of Natural Resources, 1978)
The purpose of this project has been to survey the collection of the James H. Albertson Center for Learning Resources, University of Wisconsin-Stevens Point (LRC) pertaining to the Water Resources curriculum of the University's College of Natural Resources. The survey attempted to collect and organize information about the existing collection and to improve the collection by locating deficient areas. The subject areas covered are those defined in the foreword to Selected Water Resources Abstracts as "the water-related aspects of the life, physical, and social sciences, as well as related engineering and legal aspects of the characteristics, conservation, control, use or management of water". Special·attention was given to management and engineering aspects since it was felt by water resources and library faculty that these areas needed the most upgrading. Library science literature on collection evaluation, summarized by Otterson (1972) and Bonn (1974), defines several distinct methods for collection evaluation which appear frequently and are usually-used in conjunction with one another. These are: compiling statistics, primarily on gross size of the collection; checking lists and bibliographies; applying standards related to the goals of the institution, including those related to accreditation; directly observing the collection, including getting a "feel" for it; obtaining user opinions and determining user satisfaction. Each of the methods has shortcomings which have also been widely discussed. What is agreed upon is the increasing need for better selection and evaluation procedures to meet the large amount of available information. It is not the purpose of this survey to produce a better or widely applicable technique for evaluation. A variety of techniques will be used to provide a base for future studies. One of the major concerns of the LRC is to acquire a collection adequate for its own community of users. Needs are based primarily on the purpose or mission of the library and the university. Before looking at specific portions of the collection it is necessary to gain information on users and programs. Part of the select mission of the University of Wisconsin-Stevens Point is to provide undergraduate and graduate programs in natural resources. To support this mission the LRC must provide material in sufficient depth for graduate scholarship and faculty needs. In 1977 the College of Natural Resources had 1524 majors including eighty graduate students. Of these, 187 undergraduates and an unspecified number of the graduates were in the Water Resources program (Newman, 1977). According to computerized records in the University's Registration Office there were fourteen water courses offered with a total enrollment of over eight hundred students during the 1976-77 academic year. Nine courses with a total enrollment of over five hundred students were offered in the fall 1977 semester. In addition, courses in the Biology Department which are closely allied to the water program enrolled an additional eighty students per year.